Consumer perception of the use of antibiotic drugs in society: A descriptive study - Mbu, Kristiana; AR, Nurul Izza (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2025)
Introduction: The inappropriate use of antibiotics in the community remains a major public health concern, as it can lead to treatment failure, increased risk of side effects, and the emergence of antibiotic resistance. Consumer perception plays an important role in determining whether antibiotics are used correctly. This study aims to describe consumer perceptions regarding the use of antibiotic drugs in PK IV RT 003/RW 002, Tamalanrea District, Makassar City. Methods: This descriptive study employed a survey approach using a structured questionnaire consisting of seven statements related to knowledge and perceptions of antibiotic use. A total of 44 respondents, selected through purposive sampling with inclusion criteria of being between 18 and 60 years old and having used antibiotics, participated in the study. Data were analyzed using a Likert scale scoring system and presented in percentage form to determine the perception category. Results: The findings indicate that most respondents demonstrated good perceptions of antibiotic use, with an overall score of 73.91%. Respondents generally understood that antibiotics are used to treat bacterial infections, must be taken until finished, and that improper use can contribute to bacterial resistance. However, misconceptions were still found, particularly the belief that antibiotics can treat viral infections such as colds and flu. Conclusion: Overall, consumer perceptions of antibiotic use fall into the good category. Nevertheless, certain misunderstandings persist. Continuous health education, including counseling and access to reliable health information platforms, is recommended to enhance community understanding and prevent antibiotic resistance.